TECTONIC AND SEDIMENT SUPPLY CONTROL OF DEEP RIFT LAKE TURBIDITE SYSTEMS: LAKE BAIKAL, RUSSIA: REPLY - Nelson C.H.; Escutia C.; Karabanov E.B.; Colman S.M. (My University, 2000)
Tectonically influenced half-graben morphology controls the amount and type of sediment supply and consequent type of late Quaternary turbidite systems developed in the active rift basins of Lake Baikal, Russia. Steep border fault slopes (footwall) on the northwest sides of half-graben basins provide a limited supply of coarser grained clastic material to multiple small fan deltas. These multiple sediment sources in turn laterally feed small (<10 km diameter) unchannelized sublacustrine sand-rich aprons that are deposited at the slope base on the lake floor. Gradual slopes of the southeastern ramp margins (hanging wall) of the lake basins, conversely, feed finer grained sediment from larger drainages into two different types of channelized turbidite sublacustrine fan systems: (1) small (5 20 km) laterally fed sand-rich fans sourced by local rivers, often originating from glaciated valleys; and (2) large (>65 km) axially fed elongate mud-rich fans sourced by regional exterior drainage of the Selenga River that supplies large quantities of silt. Basin plain turbidites in the center of the linear basins and axial channels that are controlled by rift-parallel faults are fed from, and interfinger with, aprons and fans. The predictability of the turbidite systems in Lake Baikal provides the best example yet studied of how tectonics and sediment supply interact to control the development of a wide variety of coeval turbidite systems on a single basin floor.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная